Write Code, Save Lives: How a Community Uses Open Innovation to Address a Societal Challenge. (23rd October 2018) - Sims, Jonathan; Gichoya, Judy; Bhardwaj, Gaurab; Bogers, Marcel
Abstract : This study explores how a community uses open innovation over time to tackle a global societal challenge. we conduct an in‐depth case study of OpenMRS, an open‐source software community providing affordable medical record‐keeping software in developing nations. We develop a process model that describes how inbound, outbound, and coupled open innovation influenced the community through four discrete phases of community development. We explain how the founders' vision led to the creation of the community, and how increasing community participation and community governance facilitated its growth. Interestingly, we found that economic opportunities made possible by open innovation may paradoxically create challenges to community sustainability. Ultimately, this study expands our understanding of open innovation communities in different settings, and their role in addressing societal challenges.